Concepts applied in daily practice in administration of medicines via nasogastric tube by the nursing team - Ingra Monique Duarte Lopes; Edson Antonio Alves da Silva; Daniela Ferreira Miyata de Oliveira; Andréia Cristina Conegero Sanches (Acta Scientiarum. Health Sciences, 2017)
The study aimed to assess the current situation of medication administration via nasogastric tube (VNGT) and identify weaknesses in the process. As a tool, the application of questionnaires to the professionals of the nursing service was used. The questionnaire contained questions and each of them, during the correction, was assigned a specific score. The participant could according to the evaluation system get a grade of 0 to 100 points. Among the participants, 66.7% stated that they had already received some guidance on medication administration via the tube, and after correction and assignment of the notes, the averages obtained were: 47.3 points by the nurses; 38.7 points by nursing technicians; 34.5 points for resident nurses; and 37.0 points by the nursing assistants. The findings of the study indicate that there is a difference between the usual practice and the recommended practice in the literature and the professionals knowledge about administration of medication VNGT is still limited. The insertion of the pharmacist in the multidisciplinary team and disseminating knowledge on incompatibilities, interactions and reactions are of great importance for the improvement of this scenario.